Aplikasi Media Pemasaran Perumahan Interaktif Berbasis Virtual Reality Tour, Augmented Reality Dan WEB Brosur: Indonesia - jajang mulyana mulyana (Universitas Majalengka, 2023)
Brochures are marketing media in the form of print media that are widely used to promote products, places, services and so on. A brochure can contain information about the products to be offered such as types, pictures, specifications and prices of products sold, so that brochures are widely used by companies that have a variety of products, because they are very helpful in promoting the products offered by the company. . The Prototype method is a Software development method that allows interaction between system developers and system users, so as to overcome incompatibility between developers and users. From the results of the evaluation of communication problems that occur the authors suggest. Using an android-based Virtual Reality Tour and Augmented reality program where Virtual Reality Tours are used as a substitute medium for the model house so that buyers can explore the marketed house without having to go to the model house directly, and Augmented reality as a substitute for 3-dimensional miniatures by using Augmented reality model 3. dimensions can be shown via a smartphone and can be easily carried during marketing Input from the marketing side so that an evaluation of the interface design is carried out so that not too many menus for information and guide menus are removed and transferred to printed brochures, the display is made simpler by displaying a house background on the main menu.